An Analysis of Word Formation of Slang Words Used in Bad Boys for Life Movie - Maulana, Mahdi Annafra; Rosa, Rusdi Noor (English Language and Literature, 2021)
This research was aimed to find the slang words and the word formation process found in Bad Boys for Life Movie. This research was descriptive qualitative research. The data were analyzed by using theory of Yule (2010) and Spolsky (2012). The data were taken from the scripts of Bad Boys Life Movie which was released in 2020. The result of the research showed that there were 82 slang words were found. Out of 10 types word formation processes, there are 7 types of found in this research. They are (40) coinage, (6) borrowing, (14) compounding, (8) blending, (11) clipping, (1) of derivation, and (2) multiple processes. The most dominant word formation process is coinage with occurrence 40 times (48.78%). The second most frequent word formation process used in creating the slang words in this movie is compounding with the occurrence 14 times (13.41%). The least dominant word formation process is derivation with occurrence 1 time (1.22%).